Paradoxical association of C-reactive protein with endothelial function in rheumatoid arthritis. - Michael V Holmes; Benyu Jiang; Karen McNeill; Melinda Wong; Stephen P Oakley; Bruce Kirkham; Phil J Chowienczyk (PLoS ONE)
Background Within the general population, levels of C-reactive protein (CRP) are positively associated with atherosclerotic cardiovascular disease (CVD). Whether CRP is causally implicated in atherogenesis or is the results of atherosclerosis is disputed. A role of CRP to protect endothelium-derived nitric oxide (EDNO) has been suggested. We examined the association of CRP with EDNO-dependent vasomotor function and subclinical measures of atherosclerosis and arteriosclerosis in patients with raised CRP resulting from rheumatoid arthritis (RA). Methodology/principal findings Patients with RA (n = 59) and healthy control subjects (n = 123), underwent measures of high sensitivity CRP, flow-mediated dilation (FMD, dependent on EDNO), intima-media thickness (IMT, a measure of subclinical atherosclerosis) and aortic pulse wave velocity (PWV, a measure of arteriosclerosis). IMT and PWV were elevated in patients with RA compared to controls but FMD was similar in the two groups. In patients with RA, IMT and PWV were not correlated with CRP but FMD was positively independently correlated with CRP (P<0.01). Conclusions/significance These findings argue against a causal role of CRP in atherogenesis and are consistent with a protective effect of CRP on EDNO bioavailability.